2018
DOI: 10.1002/adfm.201803613
|View full text |Cite
|
Sign up to set email alerts
|

Shift of the Branching Point of the Side‐Chain in Naphthalenediimide (NDI)‐Based Polymer for Enhanced Electron Mobility and All‐Polymer Solar Cell Performance

Abstract: The branching point of the side-chain of naphthalenediimide (NDI)-based conjugated polymers is systematically controlled by incorporating four different side-chains, i.e., 2-hexyloctyl (P(NDI1-T)), 3-hexylnonyl (P(NDI2-T)), 4-hexyldecyl (P(NDI3-T)), and 5-hexylundecyl (P(NDI4-T)). When the branching point is located farther away from the conjugated backbones, steric hindrance around the backbone is relaxed and the intermolecular interactions between the polymer chains become stronger, which promotes the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 89 publications
4
62
0
1
Order By: Relevance
“…Similar trend of electron mobilities was found in NDI-based small molecules but the highest mobility was achieved at the third carbon position [25] . In contrast, owing to improved polymer crystallinity, the electron mobility of NDI-based polymers would continuously increase when moving the branching position of the alkyl chains from the second to the fifth carbon position [31] . Thus it can be seen that, alkyl chain regulation is a powerful approach to tune intermolecular interaction to improve the charge carrier mobility, but on the other hand, it is still unclear how to determine an optimal length or branching position for the alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trend of electron mobilities was found in NDI-based small molecules but the highest mobility was achieved at the third carbon position [25] . In contrast, owing to improved polymer crystallinity, the electron mobility of NDI-based polymers would continuously increase when moving the branching position of the alkyl chains from the second to the fifth carbon position [31] . Thus it can be seen that, alkyl chain regulation is a powerful approach to tune intermolecular interaction to improve the charge carrier mobility, but on the other hand, it is still unclear how to determine an optimal length or branching position for the alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…For solution-processed conjugated molecules and polymers, side alkyl chains are requisite to attach onto the conjugated backbone for ensuring good solubility in organic solvents. More and more studies have shown that modulation of the introduced alkyl chains, such as different chain lengths [18][19][20][21][22] and branching positions [23][24][25][26][27][28][29][30][31][32] , can significantly change the intermolecular interaction, molecular packing, thin film morphology, and thus the charge carrier mobility and device performance. For example, the charge carrier mobility of diketopyrrolopyrrole (DPP)-based copolymers can be increased by 2-4 times upon replacing the branched alkyl chain of 2-octylododecyl with the longer chain of 2-decyltetradecyl [18] .…”
Section: Introductionmentioning
confidence: 99%
“…[61] The resulting polymer acceptors show obviously different crystallization properties, with the highest-crystalline one, PNDI2HD-T, showing the best device performance (PCE = 6%)w hen matched with ac lassic NBG p-type polymer PTB7-Th.R ecently,t he same group further expanded the strategy by tuning the branching point of side chainso fp olymer acceptors. [62] The receding of the branching point from the polymer skeleton reduced the steric hindrance and enhanced the molecularc rystallization. The resulting ntype polymerP (NDI3T) exhibited aP CE of 7.1 %f or all-PSCs based on aW BG polymer donor PBDTTTPD.…”
Section: Ndi-basedn-type Polymersmentioning
confidence: 99%
“…However,n-type polymers play acritical role in OTFTs, [6] allpolymer solar cells (all-PSCs), [7] and perovskite solar cells [8] as electron-transporting materials.T herefore,i ti su rgently needed to devise new high-performance n-type polymers with optimized optoelectronic character and film forming property to advance the performance of various organic optoelectronic devices. [9] Constructing donor-acceptor (D-A) type conjugated polymers using highly electron-deficient units,s uch as naphthalene diimide (NDI), [10] perylene diimide (PDI), [11] and B ! Ne mbedded (hetero)arene, [12] served as the most effective approach to develop high-performance n-type polymers.…”
Section: Introductionmentioning
confidence: 99%